The concept of halal and thayyib and its implementation in Indonesia - Muhammad Cholil Nafis (Universitas Airlangga, 2019)
The issue of halal and haram is regarded by Muslims as the basis concept. The word halal is derived from Arabic word, permissibility (in the sense of what is permitted in the Shariah). For Muslims, the basis of every action must be worship, which is worshipping to God Almighty. The eating activity is also a means of worship with rules and procedures according to the Sharia. The Holy Quran says eating is not just enough for halal but it should be thayyib. Therefore, the guarantee of halal products is important. The tremendous advances in science and technology in the fields of food, medicine and cosmetics are growing. This condition affects many things in the processing and use of basic ingredients. In order to keep Muslim’s food from haram contaminations, espicially from basic ingredients, the Indonesia Ulema Council (MUI) has been the pioneer in obtaining Halal certification. In Indonesia, the efforts to award Halal certificates have taken a quarter of a century. MUI has been granted a Halal certificate to ensure the nation's access to food, beverages and halal materials. MUI has also established the standards of halal according to Islamic law. The examination and study are then conducted to issue a fatwa and then a Halal certificate is issued. Halal certification process was not maximized in Indonesia because politics was not integrated and facilities and infrastructure were inadequate.